Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Nylon microfibers develop a distinct plastisphere but have no apparent effects on the gut microbiome or gut tissue status in the blue mussel, Mytilus edulis - Hannah I. Collins; Tyler W. Griffin; Bridget A. Holohan; J. Evan Ward (Environmental Microbiology, 2023)
Ingestion of microplastics (MP) by suspension‐feeding bivalves has been well‐documented. However, it is unclear whether exposure to MP could damage the stomach and digestive gland (gut) of these animals, causing ramifications for organism and ecosystem health. Here, we show no apparent effects of nylon microfiber (MF) ingestion on the gut microbiome or digestive tissues of the blue mussel, Mytilus edulis . We exposed mussels to two low concentrations (50 and 100 particles/L) of either nylon MF or Spartina spp. particles (dried, ground marsh grass), ca. 250–500 μm in length, or a no particle control laboratory treatment for 21 days. Results showed that nylon MF, when aged in coarsely filtered seawater, developed a different microbial community than Spartina spp. particles and seawater, however, even after exposure to this different community, mussel gut microbial communities resisted disturbance from nylon MF. The microbial communities of experimental mussels clustered together in ordination and were similar in taxonomic composition and measures of alpha diversity. Additionally, there was no evidence of damage to gut tissues after ingestion of nylon MF or Spartina spp. Post‐ingestive particle processing likely mediated a short gut retention time of these relatively large particles, contributing to the negligible treatment effects.

A multi‐study analysis of gut microbiome data from the blue mussel ( Mytilus edulis ) emphasises the impact of depuration on biological interpretation - Tyler W. Griffin; Mya A. Darsan; Hannah I. Collins; Bridget A. Holohan; Melissa L. Pierce; J. Evan Ward (Environmental Microbiology, 2023)
The blue mussel ( Mytilus edulis ) is a suspension feeder which has been used in gut‐microbiome surveys. Although raw 16S sequence data are often publicly available, unifying secondary analyses are lacking. The present work analysed raw data from seven projects conducted by one group over 7 years. Although each project had different motivations, experimental designs and conclusions, all selected samples were from the guts of M. edulis collected from a single location in Long Island Sound. The goal of this analysis was to determine which independent factors (e.g., collection date, depuration status) were responsible for governing composition and diversity in the gut microbiomes. Results indicated that whether mussels had undergone depuration, defined here as voidance of faeces in a controlled, no‐food period, was the primary factor that governed gut microbiome composition. Gut microbiomes from non‐depurated mussels were mixtures of resident and transient communities and were influenced by temporal factors. Resident communities from depurated mussels were influenced by the final food source and length of time host mussels were held under laboratory conditions. These findings reinforce the paradigm that gut microbiota are divided into resident and transient components and suggest that depuration status should be taken into consideration when designing and interpreting future experiments.

Recommendations for advancing test protocols examining the photo-induced toxicity of petroleum and polycyclic aromatic compounds - Matthew M. Alloy; Bryson E. Finch; Collin P. Ward; Aaron D. Redman; Adriana C. Bejarano; Mace G. Barron (Aquatic Toxicology, 2023)

Identification of next-generation International Humic Substances Society reference materials for advancing the understanding of the role of natural organic matter in the Anthropocene - Yu-Ping Chin; Diane M. McKnight; Juliana D’Andrilli; Nicole Brooks; Kaelin Cawley; Jennifer Guerard; E. Michael Perdue; Colin A. Stedmon; Paul G. Tratnyek; Paul Westerhoff; Andrew S. Wozniak; Paul R. Bloom; et al. (Aquatic Sciences, 2023)
Many challenges remain before we can fully understand the multifaceted role that natural organic matter (NOM) plays in soil and aquatic systems. These challenges remain despite the considerable progress that has been made in understanding NOM’s properties and reactivity using the latest analytical techniques. For nearly 4 decades, the International Humic Substances Society (IHSS, which is a non-profit scientific society) has distributed standard substances that adhere to strict isolation protocols and reference materials that are collected in bulk and originate from clearly defined sites. These NOM standard and reference samples offer relatively uniform materials for designing experiments and developing new analytical methods. The protocols for isolating NOM, and humic and fulvic acid fractions of NOM utilize well-established preparative scale column chromatography and reverse osmosis methods. These standard and reference NOM samples are used by the international scientific community to study NOM across a range of disciplines from engineered to natural systems, thereby seeding the transfer of knowledge across research fields. Recently, powerful new analytical techniques used to characterize NOM have revealed complexities in its composition that transcend the “microbial” vs. “terrestrial” precursor paradigm. To continue to advance NOM research in the Anthropocene epoch, a workshop was convened to identify potential new sites for NOM samples that would encompass a range of sources and precursor materials and would be relevant for studying NOM’s role in mediating environmental and biogeochemical processes. We anticipate that expanding the portfolio of IHSS reference and standard NOM samples available to the research community will enable this diverse group of scientists and engineers to better understand the role that NOM plays globally under the influence of anthropogenic mediated changes.

Rapid evolution allows coexistence of highly divergent lineages within the same niche - Ben A. Ward; Sinead Collins (Ecology Letters, 2022)
Marine microbial communities are extremely complex and diverse. The number of locally coexisting species often vastly exceeds the number of identifiable niches, and taxonomic composition often appears decoupled from local environmental conditions. This is contrary to the view that environmental conditions should select for a few locally well‐adapted species. Here we use an individual‐based eco‐evolutionary model to show that virtually unlimited taxonomic diversity can be supported in highly evolving assemblages, even in the absence of niche separation. With a steady stream of heritable changes to phenotype, competitive exclusion may be weakened, allowing sustained coexistence of nearly neutral phenotypes with highly divergent lineages. This behaviour is robust even to abrupt environmental perturbations that might be expected to cause strong selection pressure and an associated loss of diversity. We, therefore, suggest that rapid evolution and individual‐level variability are key drivers of species coexistence and maintenance of microbial biodiversity.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

How encroaching shrubs and nutrients affect N2-fixation in the Chihuahuan desert - Lauren M. Baldarelli; Scott L. Collins; David Ward (Plant and Soil, 2021)

Experimental metatranscriptomics reveals the costs and benefits of dissolved organic matter photo‐alteration for freshwater microbes - Sarah G. Nalven; Collin P. Ward; Jérôme P. Payet; Rose M. Cory; George W. Kling; Thomas J. Sharpton; Christopher M. Sullivan; Byron C. Crump (Environmental Microbiology, 2020)
Summary Microbes and sunlight convert terrigenous dissolved organic matter (DOM) in surface waters to greenhouse gases. Prior studies show contrasting results about how biological and photochemical processes interact to contribute to the degradation of DOM. In this study, DOM leached from the organic layer of tundra soil was exposed to natural sunlight or kept in the dark, incubated in the dark with the natural microbial community, and analysed for gene expression and DOM chemical composition. Microbial gene expression (metatranscriptomics) in light and dark treatments diverged substantially after 4 h. Gene expression suggested that sunlight exposure of DOM initially stimulated microbial growth by (i) replacing the function of enzymes that degrade higher molecular weight DOM such as enzymes for aromatic carbon degradation, oxygenation, and decarboxylation, and (ii) releasing low molecular weight compounds and inorganic nutrients from DOM. However, growth stimulation following sunlight exposure of DOM came at a cost. Sunlight depleted the pool of aromatic compounds that supported microbial growth in the dark treatment, ultimately causing slower growth in the light treatment over 5 days. These first measurements of microbial metatranscriptomic responses to photo‐alteration of DOM provide a mechanistic explanation for how sunlight exposure of terrigenous DOM alters microbial processing and respiration of DOM.

Access to Marine Genetic Resources (MGR): Raising Awareness of Best-Practice Through a New Agreement for Biodiversity Beyond National Jurisdiction (BBNJ) - Muriel Rabone; Harriet Harden-Davies; Jane Eva Collins; Sabine Zajderman; Ward Appeltans; Gabi Droege; Angelika Brandt; Liliana Pardo-Lopez; Thomas G. Dahlgren; Adrian G. Glover; Tammy Horton (Frontiers in Marine Science, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Trophodynamics of Protomyctophum (Myctophidae) in the Scotia Sea (Southern Ocean) - R. A. Saunders; M. A. Collins; P. Ward; G. Stowasser; R. Shreeve; G. A. Tarling (Journal of Fish Biology, 2015)
This study investigated spatial and temporal patterns in distribution, population structure and diet of Bolin's lanternfish Protomyctophum bolini , Tenison's lanternfish Protomyctophum tenisoni and gaptooth lanternfish Protomyctophum choriodon in the Scotia Sea using data collected by midwater trawl during spring, summer and autumn. Protomyctophum bolini was the most abundant species of the genus encountered throughout the Scotia Sea with the greatest concentrations occurring around the Antarctic Polar Front ( APF ). This species had a life cycle of 2+ years, but spatial differences in population structure were apparent as the I‐group was absent from all regions south of the APF , suggesting that the species does not recruit in the Scotia Sea. Protomyctophum tenisoni occurred mostly in waters characteristic of the APF and was absent from the southern Scotia Sea. It had a limited size range, but there was clear size‐related sexual dimorphism with males significantly larger than females. The species had a life cycle of c. 2 years, but the I‐group ( c. 1 year old, 1 November to 31 October the next year) occurred only in regions close to the APF suggesting that recruitment is restricted to these waters. A seasonal southward migration for P. choriodon is likely as the species occurred mostly to the south‐west of South Georgia in summer, but extended to the sea‐ice sectors in autumn. Protomyctophum choriodon had a life cycle of 4+ years in the Scotia Sea and the population was dominated by age classes >3 years old. Larval stages were absent during the surveys for all species. Diurnal variations in vertical distribution were apparent for all three species. Interspecific variations in diet were evident, but all species were primarily copepod feeders, with Metridia spp., Rhincalanus gigas and Calanus simillimus generally dominating their diet. Small euphausiids, principally Thysanoessa spp., were also an important component of their diets, particularly for P. choriodon which had the largest body size. The spatial and temporal variations in diet for both P. bolini and P. tenisoni were broadly consistent with underlying abundance patterns within the mesozooplankton community.

Distribution, population structure and trophodynamics of Southern Ocean Gymnoscopelus (Myctophidae) in the Scotia Sea - Ryan A. Saunders; Martin A. Collins; Peter Ward; Gabriele Stowasser; Rachael Shreeve; Geraint A. Tarling (Polar Biology, 2015)

The trophodynamics of Southern Ocean Electrona (Myctophidae) in the Scotia Sea - Ryan A. Saunders; Martin A. Collins; Emma Foster; Rachel Shreeve; Gabriele Stowasser; Peter Ward; Geraint A. Tarling (Polar Biology, 2014)

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Homozygous loss of menin is well tolerated in liver, a tissue not affected in MEN1 - Peter C. Scacheri; Judy S. Crabtree; Alyssa L. Kennedy; Gary P. Swain; Jerrold M. Ward; Stephen J. Marx; Allen M. Spiegel; Francis S. Collins (Mammalian Genome, 2004)

The micromorphology of selected Irish milled peats - S.J. Mooney; N.M. Holden; S.M. Ward; J.F. Collins (Plant and Soil, 2000)

Effect of a selective dopamine D 1 agonist (ABT-431) on smoked cocaine self-administration in humans - M. Haney; Eric D. Collins; Amie S. Ward; Richard W. Foltin; Marian W. Fischman (Psychopharmacology, 1999)

Morphological observations of dye tracer infiltration and by-pass flow in milled peat - S.J. Mooney; N.M. Holden; S.M. Ward; J.F. Collins (Plant and Soil, 1999)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)